The Entwined Tapestry: Iranian cinema and Islamic Revivalism (1970-1990) - Ali, Saima; Abdelaziz, Berghout (ISTAC-IIUM Publication, 2024)
The present work focuses on the relations between Iranian cinema and the Islamic Revival movement from the 1970s up to the 1990s. It examines how the Islamic revolution of 1979 affected Iranian cinematic production and its change from Western-influenced melodramas to Islam-centred narratives. It analyses how Iranian filmmakers managed to employ different film techniques to communicate religious concepts and promote contemplation. It showcases the complex relationship between religion, culture, and modernity in Iranian films, illustrating their distinct cultural value and deeper significance. This study also covers works of outstanding film directors such as Abbas Kiarostami, Mohsen Makhmalbaf, Dariush Mehrjui and Bahram Beizai whose work reflects the equilibrium between innovation and spirituality. By examining different aspects of visual style including symbolism, mise-en-scène and reflective editing, the article provides an understanding of how these directors impacted the development of the Iranian film in a time of significant cultural and ideological change. It underscores the role of cinema in Iran as a medium for projecting the country’s identity as well as an agent that informs and influences the nation’s ideology. The findings revolve around the chronicles of religion, politics and art that the film presented. By analysing such interactions, this article reveals the dynamics of the global resonance of Iranian cinema and its capacity to go beyond cultural contexts, reflecting broader themes of Islamic revivalism and cultural evolution.